Leadership and digital transformation of Peruvian companies - Reyes, Flor Angélica Lavanda; Mejia, Mario Gustavo Reyes; Acevedo, Jesus Reyes; Reyes, Rosa Elvira Ruiz; Samanamud, Luis Alberto Castillo (Eximia, 2022)
The covid 19 pandemic in Peru showed that companies were not prepared to face the new requirements of the increasingly digitized consumer and therefore on the other hand, not all leaders promote this adaptation, because they consider that there are many changes to be made, from the mentality of the workers, their training, up to the required equipment. In this study, the problem was raised: How does the leadership style influence the digital transformation of Peruvian companies?, considering that digital transformation is an essential requirement for its permanence in the market. The leader will mark the most suitable strategies to make this process possible in the shortest possible time. The study concluded that leadership style directly influences the digital transformation of Peruvian companies.